A human recombinant autoantibody-based immunotoxin specific for the fetal acetylcholine receptor inhibits rhabdomyosarcoma growth in vtro and in a murine transplantation model - Gattenlöhner, Stefan; Jörißen, H.; Huhn, M.; Vincent, A.; Beeson, D.; Tzartos, S.; Mamalaki, A.; Etschmann, B.; Müller-Hermelink, Hans Konrad; Koscielniak, E.; Barth, S.; Marx, Alexander (Journal of biomedicine and biotechnology, 2010)
Rhabdomyosarcoma (RMS) is the most common malignant soft tissue tumor in children and is highly resistant to all forms of treatment currently available once metastasis or relapse has commenced. As it has recently been determined that the acetylcholine receptor (AChR) -subunit, which defines the fetal AChR (fAChR) isoform, is almost exclusively expressed in RMS post partum, we recombinantly fused a single chain variable fragment (scFv) derived from a fully human anti-fAChR Fab-fragment to Pseudomonas exotoxin A to generate an anti-fAChR immunotoxin (scFv35-ETA). While scFv35-ETA had no damaging effect on fAChR-negative control cell lines, it killed human embryonic and alveolar RMS cell lines in vitro and delayed RMS development in a murine transplantation model. These results indicate that scFv35-ETA may be a valuable new therapeutic tool as well as a relevant step towards the development of a fully human immunotoxin directed against RMS. Moreover, as approximately 20% of metastatic malignant melanomas (MMs) display rhabdoid features including the expression of fAChR, the immunotoxin we developed may also prove to be of significant use in the treatment of these more common and most often fatal neoplasms.
Gesehen am 16.10.2023